A method of calculation of specific conductivity tensor of a anisotropic media - Vytautas Kleiza; Jonas Kleiza (Lietuvos Matematikos Rinkinys)
The article presents a method for calculating specific electrical conductivity tensor. This method is based on substantiation of uniqueness and existents theorems.